1999
DOI: 10.1046/j.1365-2648.1999.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an innovative curriculum: nursing education in the next century

Abstract: The present research focused on an interim evaluation of a new nursing curriculum made by first- and second-year undergraduates. Study 1 examined the assessments made by 90 students of the new, actual programme of their studies, as well as an ideal one, on 21 bipolar criteria reflecting the developing changes in health care practices and higher educational processes in western society. The results of study 1 indicated that students perceived the actual programme as compatible with health care changes, but lack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…14 Nursing practice in decades past has emphasized individual patient treatment and care. An evolving healthcare system challenges the nursing field to build models of care that emphasize primary prevention through health education and proactive case management 15 and that consider needs from the population perspective including a proactive role in public policy. The role of nurses within this model of healthcare thus requires leadership at the systems level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Nursing practice in decades past has emphasized individual patient treatment and care. An evolving healthcare system challenges the nursing field to build models of care that emphasize primary prevention through health education and proactive case management 15 and that consider needs from the population perspective including a proactive role in public policy. The role of nurses within this model of healthcare thus requires leadership at the systems level.…”
Section: Introductionmentioning
confidence: 99%
“…Public policies and effective management of community health and health promotion programs that are responsive to the needs of multiple stakeholders, and incorporate cost-effectiveness and outcomes-based models of evaluation require that nursing leaders utilize as well as develop evidence-based strategies for education and practice. 15 The cornerstone of leadership in the nursing profession is responsible, adaptable decision-making that is context-specific and is based on a sound conceptual and pragmatic understanding of the implications of clinical evidence and the need for clinically relevant research. 5 Preparing nurses to meet the challenges of leadership, within an emerging healthcare environment directed toward primary, secondary, and tertiary Integration of Nursing Education, Practice, and Research E3 prevention, requires the integration of research, practice, and education.…”
Section: Introductionmentioning
confidence: 99%
“…What is needed today is a curriculum revolution that challenges long-standing traditions and develops new pedagogies. These new pedagogies must be research based, flexible, responsive to diverse student populations, and aligned with the contemporary health care system (Ben-Zur, Yagil, & Spitzer, 1999).…”
mentioning
confidence: 99%
“…The curricular influence on the use of service learning has not been fully explored in the research, only four researchers addressed curriculum (Ben-Zur, Yagil, & Spitzer, 1999;Gelmon et al, 1998;Martin, 1994;Robinson & Barnett, 1996). These researchers did so from two perspectives by asking; what effect did service learning have on the curriculum, or which type of curriculum lends itself to service learning?…”
Section: External Variablesmentioning
confidence: 99%
“…They concluded that a key factor in curricular reform to include service learning is faculty involvement. In a second study, Ben-Zur et al (1999) reported that nursing curriculum changes needed to occur to assist student transition into the projected future healthcare system. However, students were surveyed for this study, not faculty.…”
Section: External Variablesmentioning
confidence: 99%